2009
DOI: 10.1093/ageing/afp204
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of frailty among community-dwelling older men and women: findings from the Hertfordshire Cohort Study

Abstract: frailty is not uncommon even among community-dwelling young-old men and women in the UK. There are social inequalities in frailty which appear to be mediated by co-morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
121
7
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(161 citation statements)
references
References 29 publications
22
121
7
11
Order By: Relevance
“…A group of researchers from the United Kingdom, for example, using data from the Cohort Study Hertfordshire, showed that frailty is partly determined by social inequality (32) .…”
Section: Discussionmentioning
confidence: 99%
“…A group of researchers from the United Kingdom, for example, using data from the Cohort Study Hertfordshire, showed that frailty is partly determined by social inequality (32) .…”
Section: Discussionmentioning
confidence: 99%
“…It is useful to have these data in females as there are more older women than men, and more frail women than men (Walston and Fried 1999;Syddall et al 2010); however, these observations need to be extended to male nonhuman primates. Although the females were presumably having menstrual cycles, observations were made without respect to time of cycle because activity levels do not vary by menstrual cycle phase in macaques or women (Barger et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, declines in physical performance as measured by such indices as muscle strength, balance, and gait speed are characteristic of aging and predictive of disability, hospitalization, and death (Era and Heikkinen 1985;Guralnik et al 1994;Guralnik et al 2000;Cesari et al 2005;Cooper et al 2010). While these measures can each contribute to the prediction of future risk, gait speed has emerged as a preferred measure because it can be reliably measured at low cost and can be easily interpreted (Cesari et al 2005;Cooper et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, the Hertfordshire Cohort Study(N=638) (35) reported an overall prevalence of 6.3 percent of community dwelling 64-74 year olds, again with a female preponderance (8.5 percent versus 4.1 percent; p=0.02). The English Longitudinal study of ageing(N=3055) (30) reported a frailty prevalence of between 8 and 13 percent for community dwelling over 65 year olds, depending on frailty measurement utilised (the Phenotype and Frailty Index definitions respectively).…”
Section: Community Settingmentioning
confidence: 99%